2013
DOI: 10.1002/jmr.2286
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus: molecular cloning of several recombinant DNase monoclonal kappa light chains with different catalytic properties

Abstract: An immunoglobulin light chain phagemid library derived from peripheral blood lymphocytes of three patients with systemic lupus erythematosus was used. Phage particles displaying DNA binding light chains were isolated by affinity chromatography on DNA-cellulose, and the fraction eluted by an acidic buffer (pH 2.6) was used for preparation of individual monoclonal light chains (MLChs, 28 kDa). Thirty three of 687 individual colonies obtained were randomly chosen for study of MLCh DNase activity. Nineteen of 33 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 65 publications
2
53
0
Order By: Relevance
“…Na + and K + suppressed DNA-hydrolyzing activity of these MLChs at different concentrations [112]. Hydrolysis of DNA by all MLChs was consistent with Michaelis-Menten kinetics.…”
Section: Lupus 64supporting
confidence: 59%
See 4 more Smart Citations
“…Na + and K + suppressed DNA-hydrolyzing activity of these MLChs at different concentrations [112]. Hydrolysis of DNA by all MLChs was consistent with Michaelis-Menten kinetics.…”
Section: Lupus 64supporting
confidence: 59%
“…In this case, 33 of 687 individual colonies were chosen randomly for study of MLChs. Nineteen of 33 clones (58%) demonstrated DNase activity [112]. Detection of DNase activity in situ after SDS-PAGE of purified MLChs using gel containing DNA showed that they are not contaminated by canonical DNases.…”
Section: Lupus 64mentioning
confidence: 98%
See 3 more Smart Citations